Extraction of gaharu esential oil using ultrasonic assisted hydrodistillation - Zubair, Mat Isa (2008)
Gaharu is one of the most highly valuable, non-timber products harvested from tropical forest that produces from the Aquilaria species trees naturally or mechanically. Its essential oil is used in varies industries as perfumes and also been used in religious occasion for centuries. The gaharu that was used in this research is grade C came from the peninsular of Malaysia and known as ‘karas’ among the locals. Recently, the gaharu essential oil traditionally extracted using hydro distillation. However, the method is not effective in producing the higher yield of oil and it is consumed a lot of time. The ultrasonic assisted hydro-distillation is introduced to enhance the process where the gaharu sample is put into an ultrasonic bath before distillate. The parameter that has been studied in this research are extraction time which are 1 hour, 3 hours, 6 hours and 9 hours, and the solid to solvent ratio which are from 1:8, 1:12, 1:16 and 1:20. Solvent been used in this research are water. From the result, it showed that the gaharu oil yield is increase along with the increase of extraction time and solid to solvent ratio and it is proved that this method are feasible to extract the gaharu oil. From the results, the highest oil yield percentage for solid to solvent ratio is for 1:20 which is 0.139 %. For extraction time, the highest percentage oil yield is for 9 hours which is 0.169 %.-Author